Tetrandrine Ameliorates Airway Remodeling of Chronic Asthma by Interfering TGF-β1/Nrf-2/HO-1 Signaling Pathway-Mediated Oxidative Stress. (3rd November 2019) - Lin, Yiping; Yao, Jingchan; Wu, Meiling; Ying, Xiaoqian; Ding, Mingxing; Wei, Yanli; Fu, Xiaoyan; Feng, Wei; Wang, Yunguang
Abstract : Background . Imbalanced oxidative stress and antioxidant defense are involved in airway remodeling in asthma. It has been demonstrated that Tetrandrine has a potent role in antioxidant defense in rheumatoid arthritis and hypertension. However, the correlation between Tetrandrine and oxidative stress in asthma is utterly blurry. This study aimed to investigate the role of Tetrandrine on oxidative stress-mediated airway remolding. Materials and Methods . Chronic asthma was established by ovalbumin (OVA) administration in male Wistar rats. Histopathology was determined by HE staining. Immunofluorescence was employed to detect the expression of α -SMA and Nrf-2. Level of oxidative stress and matrix metalloproteinases were examined by ELISA kits. Cell viability and cell cycle of primary airway smooth muscle cells (ASMCs) were evaluated by CCK8 and flow cytometry, respectively. Signal molecules were detected using western blot. Results . Tetrandrine effectively impairs OVA-induced airway inflammatory and airway remodeling by inhibiting the expression of CysLT1 and CysLTR1. The increase of oxidative stress and subsequent enhancement of MMP9 and TGF- β 1 expression were rescued by the administration of Tetrandrine in the rat model of asthma. In in vitro experiments, Tetrandrine markedly suppressed TGF- β 1-evoked cell viability and cell cycle promotion of ASMCs in a dose-dependent manner. Furthermore, Tetrandrine promoted Nrf-2 nuclear transcription and activated its downstream HO-1 in vivo and in vitro. Conclusion . Tetrandrine attenuates airway inflammatory and airway remodeling in rat model of asthma and TGF- β 1-induced cell proliferation of ASMCs by regulating oxidative stress in primary ASMCs, suggesting that Tetrandrine possibly is an effective candidate therapy for asthma.